1982
DOI: 10.1079/bjn19820042
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and changes in urease (EC3.5.1.5) activity in Rumen Simulation Technique (Rusitec)

Abstract: 1. The Rumen Simulation Technique (Rusitec) was used in a series of long-term experiments to study the distribution and changes of urease (EC 3.5. I . 5 ) activity in a heterogeneous fermentation system.2. It was shown that in Rusitec the high urease activity from the inoculum decreased to low values, that the rate of decrease was consistent with simple dilution of ureolytic micro-organisms and that the urease activity could be restored to original values by infusion of urea into the reaction vessels. The magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
3
18
0
Order By: Relevance
“…1 e), however, appeared to be confounded by somewhat unusual values recorded on treatment 3; on this treatment, supplementary urea was infused directly into the rumen and had the effect of creating unusually high concentrations of rumen NH3 (48-50 mg/ 100 ml) in the normally fed animals. Czerkawski & Breckenridge (1982) have shown that exogenous urea given by infusion stimulates urease activity in an artificial rumen system. If similar effects occur in vivo this could give rise to elevated concentrations of NH3 in the rumen and would clearly introduce some bias to the normal plasma urea-rumen NH3 relationship.…”
Section: Discussionmentioning
confidence: 99%
“…1 e), however, appeared to be confounded by somewhat unusual values recorded on treatment 3; on this treatment, supplementary urea was infused directly into the rumen and had the effect of creating unusually high concentrations of rumen NH3 (48-50 mg/ 100 ml) in the normally fed animals. Czerkawski & Breckenridge (1982) have shown that exogenous urea given by infusion stimulates urease activity in an artificial rumen system. If similar effects occur in vivo this could give rise to elevated concentrations of NH3 in the rumen and would clearly introduce some bias to the normal plasma urea-rumen NH3 relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis in the rumen by microorganisms is very closely associated with the activity of these same organisms in breaking down cellulose and other carbohydrate materials and in the formation of organic acids as byproducts of this fermentation process. Since the concentration of carbohydrate in this compartment is low, it is unlikely to be the most active metabolic site (Czerkawski and Breckenridge 1982 ). Through the years many attempts were made to determine the optimum concentrations of ammonia in the rumen and to relate it to synthesis of microbial protein.…”
Section: Ammonia Utilizationmentioning
confidence: 99%
“…In in vivo studies with sheep fed with a low-protein diet (3.7 g N/day), urease activity was found to be the highest in the bacteria adhering to the rumen wall, lower in the rumen fl uid bacteria, and lowest in the bacteria adhering to feed particles in the rumen (Javorský et al 1987 ). In rusitec fermenter study (Czerkawski and Breckenridge 1982 ), the ureolytic activity per unit volume was usually higher in compartment 2 (space occupied by microorganisms that are loosely associated with the solids) than in compartment 1 (strained rumen contents) or compartment 3 (space occupied by microorganisms that are tightly associated with solid matrix). In rusitec fermenter study (Czerkawski and Breckenridge 1982 ), the ureolytic activity per unit volume was usually higher in compartment 2 (space occupied by microorganisms that are loosely associated with the solids) than in compartment 1 (strained rumen contents) or compartment 3 (space occupied by microorganisms that are tightly associated with solid matrix).…”
Section: Introductionmentioning
confidence: 95%
“…Rusitec has no rumen wall, there is only one entry point (with saliva) and this can be controlled. A series of experiments with urea (Czerkawski & Breckenridge, 1982) have shown that the high urease activity of the inoculum declined to low, but not negligible values in Rusitec and that the urease activity could be induced at will by infusion of urea in artificial saliva; the activity was a direct function of the rate of input of urea. The addition of urea as a solid or as a concentrated solution had no effect on urease activity.…”
Section: Consequences Of Compartmentationmentioning
confidence: 99%
“…The 'structure' of compartment 2 can be studied by a very simple procedure (Czerkawski & Breckenridge, 1982). Instead of washing the bags of digesta with artificial saliva, one comer of the polyethylene bag is cut with scissors, the solid is squeezed slowly and the fractions of the associated liquid are collected (e.g.…”
Section: Model Systems In Nutritional Researchmentioning
confidence: 99%